Revisiting the question of extending the limits of protection of pharmaceutical patents and data outside the EU: The need to rebalance - Daniel Opoku Acquah (South Centre, 2020)
The European Union (EU) has instituted internal and external measures aimed at protecting and enforcing intellectual property rights. In the area of pharmaceutical patents, the Union has also sought to protect its industries through patent term extension and data exclusivity. Recent EU free trade agreements (FTAs) with developing countries contain chapters on intellectual property that extend patent terms and data exclusivity for pharmaceutical products. Such acts further prolong the lifespan of protection given to existing products and limit generic market entry. I identify the issue as one of “cross-pollination” of laws and argue that since similar laws exist in the internal regime of the EU, incorporating them into the EU would not be too technically difficult. However, to the extent that this regime is simulated in developing countries, implementation would damage the health sectors and economies of these countries. I therefore propose that developing countries should not be forced to adopt such laws through FTAs. If they are forced to adopt the laws after all, there should be a compulsory inclusion of (1) a clause on transitional arrangements for developing countries specific to intellectual property; (2) a clause that clearly links the objectives for intellectual property protection and enforcement (in this context, patent term extension and data exclusivity) to balance the promotion of technological innovation with access to medicines; and (3) a clause on Bolar exemption and a manufacturing waiver.
Keywords: 300; Access to Medicines; Biologics; Bolar; Data Exclusivity; European Union (EU); Flexibilities; Free Trade Agreements (FTAs); Generic Medicines; Health; India; Innovation; Intellectual Property; Intellectual Property (IP) Enforcement; Patent; Patent Term; Pharmaceuticals; TRIPS